RANCANG BANGUN KONSTRUKSI BODI PADA AUTOMATIC WELDING CARRIER MACHINE - Andah Lugas Dhinata; Ahmad Ali Imron; Budi Harijanto (Pustaka Poltekad, 2021)
Manually system welding process still widely used and have a deficiency in it. Which work is accident often occur in it, the unstable arc of fire and quality of welding product still depends on the welder ability. The purpose of this study is to design a portable robotic welding tool equipped MIG(Metal Inert Gas) welding tool to support automation in the welding process. Mobility and work range of tools is supported by light and strong material and designed with relatively small dimensions and equipped leg robotics which is useful to adding work range of the tool in every single welding process. This study using experimentally and simulations methods in body construction and empirical calculation to know relevantly the result and simulation process. And the data obtained after calculating with imposition 98 N, pressure stress on the body is 3334 Pa, which is smaller than the Modulus of Elasticity Aluminum alloy type 5052, moreover, materials used are capable and safe. The riveted joint of the extensions of the body has fracture resistance 2,8 kN and used efficiency of 70% moreover this kind of extensions are efficient to apply on Automatic Welding Carrier Machine’s body.